Analisis Sejarah Karya Arsitektur Bangunan Museum Benteng Vredeburg Yogyakarta - Mita Liana Sari; Dara Wisdianti (PT. Arsil Reka Engineering, 2024)
Museum Benteng Vredeburg Yogyakarta is one of the historical buildings that has high architectural and historical value. As a Dutch colonial heritage, the building originally functioned as a defense fort in the 18th century before being converted into a museum that documents the history of the Indonesian people's struggle. This research aims to analyze the architectural history of Museum Benteng Vredeburg, including its functional evolution, building design characteristics, and its relevance to the historical context and local culture. The method used in this research is a qualitative-descriptive approach, with data collection techniques in the form of literature study, direct observation, and visual analysis of building architectural elements. The results showed that Fort Vredeburg adopted a European colonial architectural style that was adapted to the tropical conditions of Indonesia, such as sloping roofs, large vents, and the use of local materials. In addition, the transformation of the building's function from a military fort to a museum reflects the changes in the historical and symbolic meanings of the building over time. The research also found that the architectural elements of the building, such as the bastion, the main gate, and the spaces inside the fort, reflect not only the construction technology of the time but also the strategic and symbolic value of Dutch colonialism in Indonesia. By changing its function as a museum, Fort Vredeburg now serves as a link between the past and the present, acting as an educational platform as well as preserving historical and architectural values.